answersLogoWhite

0

There are some operators missing that make this rather ambiguous.

If you mean:

3x - 111 + x2 = x

and wish to solve for x, then here's the answer:

x2 + 2x - 111 = 0

x2 + 2x + 1 = 112

(x + 1)2 = 112

x + 1 = ± √112

x = -1 ± 4√7

If you mean:

3x - 111 = x2 + x

Then solving for x gives us this:

x2 - 2x + 111 = 0

x2 - 2x + 1 = 112

(x - 1)2 = 112

x - 1 = ± √112

x = 1 ± 4√7

If you mean:

3x - 111 + x2 + x

And want to simplify it, that would be:

x2 + 4x - 111

Not much really, as it can't be factored further.

User Avatar

Wiki User

11y ago

Still curious? Ask our experts.

Chat with our AI personalities

RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
BlakeBlake
As your older brother, I've been where you are—maybe not exactly, but close enough.
Chat with Blake

Add your answer:

Earn +20 pts
Q: How do you slove this problem 3x-111 x2 x?
Write your answer...
Submit
Still have questions?
magnify glass
imp